Design and fabrication of test rig for static pushing and pulling experiments - Mahadzir, Muhammad Nadzirul Izzat; Halim, Isa; Zainal Abidin, Muhammad Zaimi; Abdullah, Zulkeflee; Radin Umar, Zaid @ Radin Zaid; Abdul Rahman, Muhammad Husna; Kasim, M.S. (2023)
Abstract. Muscular strength data associated with pushing and pulling forces are crucial for ergonomists to design tasks and equipment in manual materials handling. Usually, ergonomists measure pushing and pulling forces using a force gauge. Subjects participating in the pushing and pulling experiments need to grip and hold the force gauge. Additional weight from the force gauge can affect the muscular strength of the subjects, which impacts the validity and reliability of the pushing and pulling data. However, research on the design and fabrication of test rigs for facilitating pushing and pulling experiments seems to be scarce. This study aimed to design and fabricate a test rig to facilitate ergonomists and subjects in performing symmetric two-handed static pushing and pulling experiments. To